Spiritual Care in Action for Oncology Patients in the uMgungundlovu and eThekwini Health Districts, KwaZulu-Natal, South Africa: A Qualitative Study - Vashni Sewkarran MN, BCur, RM, RN; Emelda Zandile Gumede PhD, MCur, RNE, RM, RN2 (SAGE Open Nursing, 2023)
Introduction Globally the inclusion of spiritual activities has been well adopted into nursing care. Empirical work related to the inclusion of spiritual activities in nursing within the South African context particularly within the oncology setting is sparse. Being diagnosed with cancer can be unsettling because of the severity and vigorous treatment that one has to endure. Spiritual activities could be used as one of the coping strategies for cancer patients in times of spiritual distress. Strengthening spiritual care by including spiritual activities into daily nursing care could be beneficial to the patient and the institution. Objective This study aimed to explore spiritual activities that could strengthen spiritual care in oncology nursing practice. Methods The research study followed a phenomenological qualitative descriptive design. The study population consisted of professional nurses working in the oncology units for more than 6 months. Four health care institutions were purposively selected. Data was collected through individual in-depth interviews and field notes. Ten professional nurses were recruited at the point of data saturation. Data analysis followed inductively using content analysis enrolling steps from Elo and Kyngas. Results The findings revealed the nurse's willingness to embrace spiritual care in action into their daily nursing care. Three subthemes: holding patient's hands, hospital policy for patient visits, and music therapy outline how patients are comforted by nurses. Conclusion Nurses are integral in the provision of spiritual care for cancer patients from diagnosis up until the end of life. The essence of spiritual activities gives patients a distraction and an escape from their pain and predicament thus improving their quality of life. The findings provide policy makers with an indication that patients do not only need medical and physical care but spiritual care in their nursing care plan.